Pengaruh Penambahan Surfaktan Gum Arabic Terhadap Sifat Fisik dan Stabilitas Fluida Nano Titania (TiO2) - Yulia Safitri; Irwan Irwan; Cut Aja Rahmawati (Jurnal Teknologi, 2021)
This study aims to examine the physical properties of titania (TiO2) by adding arabic gum surfactants to obtain stable nanofluid. Nano titania fluid preparation was carried out by dispersing titania nanoparticles and arabic gum in a homogenizer for 3 hours with particle variations in fraction volume and arabic gum surfactant concentration. The study was carried out by varying the volume of the particle fraction at 0.1%; 0.2%; 0.3%; 0.4% and 0.5% and arabic gum surfactant concentrations at 1%; 2%; 3%; 4%; and 5%. Measurements are also made at a temperature variation of 30 OC; 40 OC; and 50 OC. Measurement of physical properties is carried out by measuring the properties of electrical conductivity, density, viscosity, and stability of titania nanofluid. The measurement results indicate that the higher the concentration of surfactant and the volume fraction of particles, the electrical conductivity, density, and viscosity of nano titania fluid is increasing. Increased temperature will reduce the viscosity of titania nanofluid.